"Looking back (and forth)": Acknowledging the people who make personal narratives plausible. Issue 1 (February 2017) - Wright, Richard Keith
Highlights: Personal narratives, including creative non-fiction and autoethnography, allow authors to make sense of the legacies created by lived experiences. The completion of a philosophical thesis is a life-changing personal experience that cannot be completed alone. Evocative autoethnographers produce creative non-fiction to challenge our understanding of the multiple socially-constructed worlds we inhabit. Abstract: The past decade has seen a noticeable rise in the number of people embracing autoethnography as an "alternate" research methodology. As a result, a plethora of first-person narratives and pieces of creative non-fiction now exist for truth-seeking scholars to access for authentic inspiration. The author's unique contribution to the ongoing conversations was first inspired by the professional confessions of a friend and former colleague. Sociological introspection, packaged as a piece of creative non-fiction, should stimulate sociological imagination, evoking a memorable, equally meaningful reaction. In this paper, the author's goals is to inspire rather than inform, encouraging readers to take time to think about their sport management memories and the meanings attached to their sport management experiences. Readers should question the plausibility of producing professional narratives of self. Readers are encouraged to have a conversation between themselves and the various leaders, legends, and legacy-makers they have followed in order to become who they are. The author encourages readers to reflect on the things they have seen, the places they have been, and the lived experiences they have produced along the way. Readers are prompted to consider the costs and consequences of presenting autoethnography through the guide of creative non-fiction.